2019
DOI: 10.21315/aamj2019.24.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Brand Orientation and Knowledge Creation on Organisational Performance of Malaysian Tourist Resorts

Abstract: The purpose of this paper is to examine the effects of brand orientation and knowledge creation process on the organisational performance of tourist resorts from the perspective of tourism entrepreneurs. Despite a plethora of branding and knowledge management literature, a limited number of studies have investigated the effects of brand orientation and knowledge creation process together on organisational performance. The studied tourism entrepreneurs exhibit low involvement in branding activities and knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Thus, market (customer and competitor) orientation may cause a business to turn into a brand-oriented one over time. Studying the importance of brand orientation in hospitality enterprises, Liow et al (2019) concluded that brand orientation enhances organizational performance. The study conducted by Liow et al (2019) and Urde's (1999) assumptions that brand orientation is built upon market orientation reveal that brand orientation, like market orientation, would affect service improvement behavior positively.…”
Section: H2: Competitor Orientation Affects Service Improvement Positivelymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, market (customer and competitor) orientation may cause a business to turn into a brand-oriented one over time. Studying the importance of brand orientation in hospitality enterprises, Liow et al (2019) concluded that brand orientation enhances organizational performance. The study conducted by Liow et al (2019) and Urde's (1999) assumptions that brand orientation is built upon market orientation reveal that brand orientation, like market orientation, would affect service improvement behavior positively.…”
Section: H2: Competitor Orientation Affects Service Improvement Positivelymentioning
confidence: 99%
“…Studying the importance of brand orientation in hospitality enterprises, Liow et al (2019) concluded that brand orientation enhances organizational performance. The study conducted by Liow et al (2019) and Urde's (1999) assumptions that brand orientation is built upon market orientation reveal that brand orientation, like market orientation, would affect service improvement behavior positively. Since market orientation affects brand orientation positively (Laukkanen et al, 2016), the mediating effect of brand orientation can be observed in the relationship between market orientation and service improvement.…”
Section: H2: Competitor Orientation Affects Service Improvement Positivelymentioning
confidence: 99%
See 1 more Smart Citation